Segmentation Model of Customer Lifetime Value in Small and Medium Enterprise (SMEs) using K-Means Clustering and LRFM Model - Fitri Marisa; Sarifah Shakinah Syed Ahmad; Zeratul Izzah Mohd Yusof; Fachrudin Hunaini; Tubagus Mohammad Akhriza Aziz (International Journal of Integrated Engineering, 2019)
The CLV model is a measure of customer profit for a company that can be used to evaluate the future value of a customer. The CLV model is a measure of customer profit for a company that can be used to evaluate the future value of a customer. This study aims to obtain Customer Lifetime Value (CLV) in each customer segment. Grouping uses the K-Means Clustering method based on the LRFM model (Length, Recency, Frequency, Monetary). The cluster formation process uses the Elbow Method and SSE with the best number of clusters = 2 clusters. CLV values are generated from the multiplication of the results of normalization of LRFM and the LFRM weight values are then summed, and carried out on each cluster that has been formed. The highest ranking among the 2 clusters is at the second cluster with the CLV value being far the highest from the other cluster average of 0.362. Based on LRFM matrix, this cluster has a high loyalty value with the symbol LRFM L ↑ R ↑ F ↑ M ↑ which is a loyal customer (the best segment that has high customer loyalty value). Based on the LRFM symbol, the company can make a strategy to retain customers and acquire customers to become loyal customers with high profitability.